(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
The chemical machinery of vegetables offers a great diversity of biological properties and plays a fundamental role in the field of pharmacology. The search for new drugs with fewer adverse effects represents a challenge for researchers. The objective of the present work was to carry out to investigate the medicinal properties and safety of extracts and essential oil from aerial parts of Clinopodium gilliesii (muña muña) and evaluate their antioxidant and anti-inflammatory activities in vivo. The extractions were carried out serially, using 96º alcohol (EE) and boiled distilled water (AE). The essential oil (EO) was obtained by steam dragging. The AE in vivo anti-inflammatory activity was determined by carrageenan induced plantar edema (acute inflammation) and granuloma formation by cotton disc (chronic inflammation) at oral doses of 250 and 500 mg/kg while that of the EO was established topically at doses of 50, 100µl/kg. In-vitro antioxidant activity was evaluated by DPPH depuration and inhibition of lipid peroxidation (β-carotene-linoleic acid method). Chemical study of the extracts was carried out by means of phytochemical screening and the essential oil was analyzed by GC-MS chromatography. The safety was evaluated with test of acute toxicity (48 h) and acute dermal toxicity (14 days). The results revealed that EE and EO had a significant acute and chronic anti-inflammatory activity, compared with positive patterns. EE (500 mg/kg), EO (100µl/kg), ibuprofen (100 mg/kg) and meprednisone (5 mg/kg) significantly reduced the weight of the exudate and cotton disc granuloma (24.17, 35.30, 45.56 and 57.17% respectively). The alcoholic and aqueous extracts presented important antioxidant activities with values higher than 90% (from 400μg/ml) in both methods and similar to the positive patterns (BHT and quercetin). The chromatographic profile of volatile oil compounds showed a great richness in terpene substances, pulegone, menthone and neomenthol, being its major constituents. The hydroalcoholic extracts revealed the presence of reducing compounds, polysaccharides, tannins, triterpenes, sterols and coumarins as major phytoconstituents. In the acute toxicity study, a single dose of 4000 and 8000 mg/kg b.w., produced no mortality and no clinical signs of disease were observed after 48 h. The essential oil at a single dose of 2000 and 5000 mg/kg of body weight did not produce treatment-related signs of toxicity or mortality in all rats tested during the 14 day observation period. These findings are encouraging to continue studies for the validation of popular use and development of a phytopharmaceutical with medicinal utility.